Collective rationality of group decisions in collaborative engineering. (27th July 2009) - Lu, Stephen C-Y.
Collaborative engineering is a dynamic socio-technical activity where a team of stakeholders works collaboratively to make group decisions based on collective rationality. This paper examines various impossibility conditions and possibility requirements for the existence of collective rationality from both theoretical and practical standpoints. Arrow's Impossibility Theorem is examined in light of the special characteristics of collaborative engineering problems. Since from a theoretical standpoint, no social welfare function can satisfy Arrow's rationality conditions of group decisions, this paper suggests some practical methods to guide collaborative engineering teams through teamwork and task-work iterations to approach collective rationality systematically when making group decisions.